2017
DOI: 10.1002/star.201600352
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of α-amylase on eggshell membrane and Ag-nanoparticle-decorated eggshell membrane for the biotransformation of starch

Abstract: Enzyme biocatalysts are very sensitive to environmental conditions. To improve their stability and operational lifetime, free enzymes are usually immobilized on a solid support. In this study, α‐amylase was immobilized on eggshell membrane (ESM) and Ag‐nanoparticle‐decorated eggshell membrane (AgNP/ESM) using glutaraldehyde as a cross‐linking agent. After immobilization, enzyme loading, activity, kinetic parameters, reusability, and storage stability were investigated. The AgNP/ESM possessed a larger enzyme lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…This observation might be ascribed to the fact that the pore size of the outer side of the ESM-strip, the inner shell membrane, is lower than that of the outer side of ESM-A0.5 and ESM-E0.9, outer shell membrane as reported previously. 31,45,49 However, despite these observations, there are no significant difference among the three types of extracted membranes (p ¼ 0.2540) when compared directly. The fluid absorption capacity of the extracted membranes was assessed at the 1 and 24-h timepoint.…”
Section: Fluid Handling Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…This observation might be ascribed to the fact that the pore size of the outer side of the ESM-strip, the inner shell membrane, is lower than that of the outer side of ESM-A0.5 and ESM-E0.9, outer shell membrane as reported previously. 31,45,49 However, despite these observations, there are no significant difference among the three types of extracted membranes (p ¼ 0.2540) when compared directly. The fluid absorption capacity of the extracted membranes was assessed at the 1 and 24-h timepoint.…”
Section: Fluid Handling Propertiesmentioning
confidence: 89%
“…Interestingly, these results are in conformity with previous reports in the literature. 18,21,45 Elemental/chemical composition EDS analyses was used to determine the elemental composition of the membranes in order to profile remaining residues following the extraction process.…”
Section: Morphologymentioning
confidence: 99%
“…Dissolution with acids also produces the eggshell membrane as a byproduct (Figure 4). Eggshell membrane is not only a cost-effective source of collagen and hyaluronic acid for the pharmaceutical and cosmetic industries [66,83], but unlike the calcified matrix, it has great potential to be used as a carrier for enzyme immobilization [65,72,[83][84][85][86]. This is supported by many studies focused on the development of biosensors based on the immobilization of enzymes on an eggshell membrane as solid carrier [73,83,[87][88][89][90][91][92][93][94][95][96].…”
Section: Carriers Based On Eggshell Membranesmentioning
confidence: 99%
“…Amylases are enzymes that provide the formation of various products such as dextrin, maltose, and glucose by hydrolyzing instance, Du et al immobilized -amylase on the eggshell membrane and Ag-nanoparticle-decorated eggshell membrane. [25] The authors reported that the pH tolerance and thermal stability of immobilized -amylase were better than those of the free counterpart. In another investigation, Radovanović and co-workers suggested magnetic particles coated with polyaniline as support for -amylase adsorption and immobilized -amylase displayed very good stability in terms of pH, temperature, and storage.…”
Section: Introductionmentioning
confidence: 99%